The Hecht vault performed at the 1995 World Gymnastics Championships: deterministic model and judges' scores - Takei, Y.; Blucker, E. P.; Nohara, H.; Yamashita, N. (Journal of Sports Sciences, 2000)
The aim of this study was to determine the mechanical variables that govern success of the Hecht vault. The participants were 122 male gymnasts from 30 countries performing the vault at the 1995 World Gymnastics Championships. The vaults were filmed using a Photosonics 16-mm motion picture camera operating at 100 Hz. Approximately 80 frames were digitized for each vault analysed. The method of Hay and Reid was used to develop a theoretical model to identify the mechanical and physical variables that determine linear and angular motions of the vault. Correlational analysis was used to establish the strength of the relationship between the causal mechanical variables identified in the model and the judges' scores. Significant correlations (P < 0.005) indicated that the following were important determinants of success: large horizontal and vertical velocities at take-off from the board and the horse; large vertical and angular distances of pre-flight; large vertical impulses of high force and short duration exerted on the horse and the resulting large changes in vertical velocity on the horse; and large horizontal and vertical distances and long times of post-flight. Of the 18 significant variables identified in the present study, the angular distance of pre- and post-flights, the horizontal velocity and angular momentum at take-off from the horse, and the average moment of inertia and duration of post-flight collectively accounted for 57% of the variation in the judges' scores.